Multimodal exploration of civic stance in the English Language Arts classroom. Issue 1 (2nd May 2017) - Doerr-Stevens, Candance
Abstract : Purpose: This study/paper aims to explore civic participation within multimodal expression. With the rise of content produced and circulated within participatory cultures online, there has been much attention raised regarding questions of audience and attention to this content. For example, does production of media content constitute having a voice if no one is paying attention? Design/methodology/approach: Using multimodal analysis and mediated discourse analysis, this study examines adolescents' school-based media production and use of multimodal ensembles to recruit and maintain audience attention to specific content in their radio and video documentaries. Findings: Research findings reveal deliberate attempts to connect with audience needs when creating media as well as exploration of emerging civic identities. Research limitations/implications: Questions for how researchers in literacy and learning can further investigate and articulate civic engagement and advocacy are suggested. Practical implications: Implications for how teachers can use multimodality to create spaces for civic engagement are provided. Originality/value: This study is original in that few studies have applied the concepts of participatory politics to media products and process conducted in school settings. This study begins to test the utility of these constructs.